Correspondence of Diarmuid Lynch with Seamus Burke regarding John Devoy, bond certificates and the Friends of Irish Freedom, - Lynch, Diarmuid, 1878-1950 (1947)
Letter and reply from Lynch relate to a letter in the 'Irish Press' regarding Judge Cohalan and the raising of a loan for the early Irish state in New York.